Citra Lansia dalam Film ‘An’ (Selai Kacang Merah) dan ‘Oke Roujin!’ (Golden Orchestra) - Febriyani, Lili (KIRYOKU, 2021)
People who have entered the final phase of life or elderly people, are often labeled with negative stereotypes regarding physical, psychological, and sociological changes. Various descriptions of the self-image of the elderly appear in various texts. This article discusses the image of the elderly in two Japanese films, entitled An (Sweet Bean) and Oke Rojin! (Golden Orchestra). By using Activity Theory, Successful Aging, and Loneliness, the research tries to analyze the image of the elderly that is constructed individually and in groups using the Content Analysis method. From the results of a thorough analysis of the components in the film, it can be concluded that the positive image of the elderly is constructed by looking for gaps of excellence from the shortcomings they have, and the positive image does not eliminate the depiction of the negative image. The elderly from both films try to make good use of old age, leaving the works in different ways, namely Tokue Yoshii with his red bean butter and the elderly orchestra with their first music and concerts.